Pelatihan Broker melalui Simulasi Roleplay untuk Meningkatkan Prospek Nasabah Baru pada TPFx - Nurdiansyah, Mochammad Irsad; Rini, Hesty Prima (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was motivated by the lack of product understanding and communication skills among intern students who served as marketing or business development officers at PT. Trijaya Pratama Futures (TPFx). The purpose of this community service activity was to improve student competency in dealing with potential customers through roleplay training and implementing the 4P Marketing Mix strategy. The implementation method of this community service activity was carried out through roleplay simulation training and the implementation of the 4P Marketing Mix strategy, with stages of preparation, implementation, and evaluation during the 4-month internship duration at PT. Trijaya Pratama Futures branch office in Surabaya. The results of the implementation showed a significant increase in self-confidence, communication skills, and also success in prospecting with customers. This activity provided direct benefits in the form of improving the quality of human resources and contributing to the success of the Company's marketing.